The trace formula for Sturm-Liouville operator with operator coefficient - Adigüzelov, E; Avci, H; Gül, E (AMER INST PHYSICS, 2001)
We will obtain a formula for the trace of the Sturm-Liouville operator with operator coefficient. (C) 2001 American Institute of Physics.
Keywords: Physics